Additive Effect of Inhaled Corticosteroid (ICS) On Patients with COPD Receiving Long-Acting Muscarinic Antagonist (LAMA)/Long-Acting Β2-Agonist (LABA): A Single-Center Observational Study. Issue 1 (June 2020) - Tanaka*, Yosuke; Yuasa, Mizuki; Hino, Mitsunori; Seike, Masahiro; Gemma, Akihiko
No abstract available